Anti‐inflammatory activity of lanoconazole, a topical antifungal agent. Issue 4 (10th February 2015) - Uratsuji, Hideya; Nakamura, Aki; Yamada, Yoshihito; Hashimoto, Kei; Matsumoto, Tatsumi; Ikeda, Fumiaki; Ishii, Ritsuko
Summary Topical antifungal agents which have anti‐inflammatory effects have the potential to provide additional clinical benefits. Therefore, an anti‐inflammatory activity of lanoconazole (LCZ), a topical antifungal agent, was investigated against in vitro and in vivo models of inflammation. The release of interleukin‐8 (IL‐8) from human epidermal keratinocytes stimulated by the addition of 100 μg ml−1 β‐glucan of Saccharomyces cerevisiae was significantly inhibited by LCZ at the concentration of 10−5 mol l−1. The release of interferon‐γ and IL‐2 from human peripheral blood mononuclear cells stimulated by the addition of 30 and 100 μg ml−1 phytohemagglutinin was significantly inhibited by LCZ at the concentrations of 10−7 and 10−6 mol l−1, respectively. The increase in the ear thickness induced by topical application of 0.01% 12‐O‐tetradecanoyl phorbol‐13‐acetate and 1% 2, 4, 6‐trinitrochlorobenzene (TNCB) after sensitisation with 3% TNCB were established as the mouse models of irritant and contact dermatitis, respectively. Application of 1% and 3% LCZ showed a significant anti‐inflammatory activity against both the irritant and contact dermatitis models. These findings suggest that LCZ possesses an anti‐inflammatory activity, which may be partially helpful in the treatment of dermatomycoses.